Bioactive Components and Radical Scavenging Activity in Selected Advance Lines of Salt-Tolerant Vegetable Amaranth - Sarker, Umakanta; Hossain, Md. Nazmul; Iqbal, Md. Asif; Oba, Shinya (Frontiers in Nutrition, 2020)
Four selected advance lines of salt-tolerant vegetable amaranth were evaluated for proximate, nutraceuticals, pigments, phytochemicals, and antioxidants components antioxidants activity in completely randomized block design (RCBD) design in three replicates. Salt-tolerant vegetable amaranth contained adequate carbohydrates, protein, moisture, and dietary fiber. The remarkable contents of iron, manganese, copper, zinc, sodium, molybdenum, boron, potassium, calcium, magnesium, phosphorus, sulphur, betacyanins, betalains, betaxanthins, chlorophylls, ascorbic acid, polyphenols, flavonoids, and antioxidant potentiality were found in salt-tolerant vegetable amaranth. The genotypes LS7 and LS9 had abundant proximate, nutraceuticals, pigments, phytochemicals, and antioxidants compared to the genotypes LS3 and LS5. Salt-tolerant vegetable amaranth demonstrated high content of ﬂavonoid compounds including flavonols such as rutin, kaempferol, isoquercetin, myricetin, hyperoside, and quercetin, flavanol, such as catechin, flavone such as apigenin, and flavanone, such as naringenin. For the first time, we identified one flavonol such as myricetin, one flavanol, such as catechin, one flavone such as apigenin, and one flavanone, such as naringenin in salt-tolerant vegetable amaranth. Across six flavonols, rutin and quercetin were identified as the most prominent compounds followed by isoquercetin and myricetin in selected salt-tolerant vegetable amaranth. Across the genotypes, LS7 exhibited the highest flavonols such as rutin, kaempferol, isoquercetin, myricetin, hyperoside, and quercetin as well as the highest flavanols, such as catechin, flavones such as apigenin, and flavanones, such as naringenin. It revealed from the correlation study that antioxidant components of salt-tolerant vegetable amaranth genotypes exhibited good radical quenching capacity of 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) and 2,2- Diphenyl-1-picrylhydrazyl equivalent to Trolox. The two genotypes LS7 and LS9 of vegetable amaranth containing excellent sources of proximate, nutraceuticals, pigments, phytochemicals, and antioxidants components could be used as potent antioxidants to attaining nutrients and antioxidant sufficiency in the saline prone area of the globe. We can extract colorful juice from the genotypes LS7 and LS9 as drink purposes for consuming the nutraceuticals and antioxidant deficient community in the saline prone area around the world. However, further details experimentation is required to confirm the standardization and stabilization of functional components of vegetable amaranth for extraction of juice as drinks.